A Critical Discourse Analysis of the Reporting of Some Niger-Delta Issues in Selected Nigerian Newspapers, 1999 – 2007 - Ayoola, Kehinde Adewale (2015)
This study examined the setting, topics and participants that were projected in the content and context of reports on the Niger-Delta in selected Nigerian newspapers. It examined the salient linguistic features employed by the writers in their presentations and critically analysed the pragmatic and discourse strategies employed by the participants in the news reports. These were done with the aim of proposing an analytical framework for describing and interpreting Nigerian print media-political discourse.